Leaps of Knowledge - Teixeira, Antonio R. L. (Advances in Social Sciences Research Journal, 2024)
Chagas Disease is the main cause of heart failure in the Western Hemisphere. Initially restricted to the American continent, the people’s migration to the Northern Hemisphere caused the disease to become present in the five continents. A scientific revolution occurs when an important discovery removes an obstacle to the serial production of new scientific knowledge of social interest. Such a revolution creates a paradigm accepted after experimental analysis and verification by scientists investigating the subject. An example of a leap in knowledge was the discovery of the protozoan Trypanosoma cruzi, its invertebrate and vertebrate hosts, an agent of a new human disease recognized by Dr. Carlos Chagas at the beginning of the twentieth century. Certainly, the seminal work of Carlos Chagas inseminates enthusiasm that is essential to disturb the minds of scientists who produce leaps of knowledge about recondite aspects of Chagas disease at the University of Brasilia.